TINJAUAN YURIDIS TUNJANGAN HARI RAYA BAGI OJEK ONLINE BERDASARKAN SURAT EDARAN KEMENTRIAN KETENAGAKERAAN REPUBLIK INDONESIA - Cahyana Effendi, Muhammad Aldo; Khasanah, Dian Ratu Ayu Uswatun; Pongantung, Ronald Jolly (Universitas Stikubank, 2025)
Religious Holiday Allowance is a mandatory worker's right that companies in Indonesia must fulfill as part of their legal responsibilities, which should also extend to online motorcycle taxi drivers. The platform worker status of online motorcycles taxi, who are typically bound only by work agreements, raises questions regarding their entitlement to this Religious Holiday Allowance. This paper aims to highlight the Circular Letter from the Ministry of Manpower Number M/3/HK.04.00/III/2025, which regulates the provision of Religious Holiday Allowance for online motorcycles taxi in the form of a religious holiday bonus. Using a socio-legal research method, this writing emphasizes the correlation between prevailing laws and regulations concerning the Religious Holiday Allowance for online motorcycles taxi drivers. The research findings indicate that online motorcycle taxi drivers have not comprehensively received their Religious Holiday Allowance rights due to their legal status as partners not being formally recognized within prevailing labor regulations. Furthermore, Circular Letter Number M/3/HK.04.00/III/2025 is non-binding, making the implementation of religious holiday bonus provisions contingent upon the individual policies of each platform company.